2004
DOI: 10.1016/j.jasms.2004.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Structural determination of neutral O-linked oligosaccharide alditols by negative ion LC-electrospray-MSn.

Abstract: Neutral O-linked oligosaccharides released from the salivary mucin MUC5B were separated and detected by negative ion LC-MS and LC-MS 2 . The resolution of the chromatography and the information obtained from collision induced dissociation of detected [M Ϫ H] Ϫ ions were usually sufficient to identify the sequence of individual oligosaccharides, illustrated by the fact that 50 different oligosaccharides ranging from disaccharides to nonasaccharides could be assigned from the sample. Fragmentation was shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
135
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(143 citation statements)
references
References 26 publications
7
135
0
1
Order By: Relevance
“…The (1-3)-linked residues, or those with a blocked hydroxyl group in the 3-position, produce a C-type cleavage at the reducing side and a Z-type cleavage at the nonreducing side, a combination that is now termed D-type [10]. It is common to release O-linked glycans as reducing end alditols, and it has been demonstrated that abundant Z-type fragment ions are formed from dissociation of negatively charged precursor ions generated from asialo structures [25].…”
mentioning
confidence: 99%
“…The (1-3)-linked residues, or those with a blocked hydroxyl group in the 3-position, produce a C-type cleavage at the reducing side and a Z-type cleavage at the nonreducing side, a combination that is now termed D-type [10]. It is common to release O-linked glycans as reducing end alditols, and it has been demonstrated that abundant Z-type fragment ions are formed from dissociation of negatively charged precursor ions generated from asialo structures [25].…”
mentioning
confidence: 99%
“…The biosynthetic precursor of the non-sulfated core 2 structure with the composition Hex 2 HexNAc 2 ([M Ϫ H] Ϫ ions of m/z 749) was identified as a single isomer ( (Fig. 5A, inset) (50). Thus, this structure was annotated as the core 2 O-glycans, Gal␤1-4GlcNAc␤1-6(Gal␤1-3)GalNAc␣1- (50).…”
Section: O-linked Oligosaccharides Of Synovial Lubricin Are Likely Tomentioning
confidence: 99%
“…5A, inset) (50). Thus, this structure was annotated as the core 2 O-glycans, Gal␤1-4GlcNAc␤1-6(Gal␤1-3)GalNAc␣1- (50). Sulfated structures were also detected and sequenced after desialylation.…”
Section: O-linked Oligosaccharides Of Synovial Lubricin Are Likely Tomentioning
confidence: 99%
“…In particular, in proteomics and glycoproteomics, nanoESI MS n in the positive as well as in the negative ion mode was shown to be capable of sequencing minute amounts of biological material thus providing straightforward information on various structure determinants. [1][2][3][4][5] Miniaturized analytical instrumentation is attracting growing interest in chemical, biochemical and structural analysis. Nowadays, various mass spectrometer configurations are interfaced to the integrated micro-and nanosystems or to devices providing either robotized sample infusion or a combination of automated sample delivery and chip-based ionization.…”
Section: Introductionmentioning
confidence: 99%